Semiotic Analysis of Visual and Auditory Framing in Film Art: A Critical Synthesis of Bordwell, Thompson, and Barthes’ Theories (Universitas Pendidikan Indonesia, 2025)
This study scientifically explores the elements of visual and auditory framing through the theoretical perspectives of David Bordwell and Kristin Thompson. The objective of this research is to uncover the processes involved in the formation of symbols and meanings in the art of film. To achieve this, a qualitative research approach is employed, utilizing a literature study model. Data is gathered from scholarly journal articles and books that discuss the ideas of Bordwell, Thompson, and Barthes, as well as topics related to visual and auditory framing in film art and semiotic analysis in cinema. All collected data is analyzed and structured through the semiotic perspective of Roland Barthes, serving as a methodological framework for understanding the formation of symbols and meanings within a film work. The study finds that through visual and auditory framing—such as cinematography, mise-en-scène, sound effects, and film scoring—a text is constructed and presented to the audience. Through semiotic analysis, this text is deconstructed using the theories of connotation, denotation, myth, signifier, and signified, resulting in the emergence of symbolic forms. These symbols are then interpreted by viewers based on their individual life experiences, leading to the creation of meaning. This process fosters a new awareness that can serve as a foundational reference or guideline for both film studies and film production.